Temporality, informality, & translocality in Africa’s urban archipelagos - Landau, Loren B. (Merian Institute for Advanced Studies in Africa (MIASA), 2019)
Mobilities across time and space are reshaping African lives, communities, and imagination. As people make lives across multiple sites – connections forged through travel, media and the circulation of goals, memories and values – they generate novel forms of mobile urbanism and belonging. Cities’ rapidly expanding, diversifying, and mobile urban populations now interact with each other in ways largely unstructured by state regulations or hegemonic social norms. The results are urban socialities often deviating from the models of solidarity, integration, and membership described in classic urban sociology or more recent debates around transnationalism, multiculturalism, and urbanization. While often appearing deeply anomic, fragmented, and relatively unregulated by officials or constitutional orders, these are not genetically antisocial or disconnected sites. Nor are they singular in the histories, morphologies or trajectories. Yet despite the diversity and distance between them, they are linked. These connections draw together urban estuaries where highly fluid populations move into and through cities with archipelagos of people and sites interlinked across and within spatial and temporal horizons. These changing social and urban forms raise epistemological, ethical, and practical challenges around the governance of space, rights, and representation. This paper outlines these concerns as a way of charting research directions for the study of mobile urbanisms.
Keywords: Human Mobility; Urbanisation; Belonging; Urban Archipelagos